Effects of knockout of the receptor for advanced glycation end‐products on bone mineral density and synovitis in mice with intra‐articular fractures. Issue 9 (24th May 2018) - Seol, Dongrim; Tochigi, Yuki; Bogner, Ashley M.; Song, Ino; Fredericks, Douglas C.; Kurriger, Gail L.; Smith, Sonja M.; Goetz, Jessica E.; Buckwalter, Joseph A.; Martin, James A.
ABSTRACT: Our group employed the mouse closed intra‐articular fracture (IAF) model to test the hypothesis that the innate immune system plays a role in initiating synovitis and post‐traumatic osteoarthritis (PTOA) in fractured joints. A transgenic strategy featuring knockout of the receptor for advanced glycation end‐products (RAGE −/− ) was pursued. The 42 and 84 mJ impacts used to create fractures were in the range previously reported to cause PTOA at 60 days post‐fracture. MicroCT (μCT) was used to assess fracture patterns and epiphyseal and metaphyseal bone loss at 30 and 60 days post‐fracture. Cartilage degeneration, synovitis, and matrix metalloproteinase (MMP‐3, ‐13) expression were evaluated by histologic analyses. In wild‐type mice, μCT imaging showed that 84 mJ impacts led to significant bone loss at 30 days ( p < 0.05), but recovered to normal at 60 days. Bone losses did not occur in RAGE −/− mice. Synovitis was significantly elevated in 84 mJ impact wild‐type mice at both endpoints (30 day, p = 0.001; 60 day, p = 0.05), whereas in RAGE −/− mice synovitis was elevated only at 30 days ( p = 0.02). Mankin scores were slightly elevated in both mouse strains at 30 days, but not at 60 days. Immunohistochemistry revealed significant fracture‐related increases in MMP‐3 and −13 expression at 30 days ( p < 0.05), with no significant difference between genotypes. These findings indicated that while RAGE −/− accelerated recovery from fracture and diminished synovitis, arthritic changes were temporary and too modest to detect an effect on the pathogenesis of PTOA. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2439–2449, 2018.